Implementation of Lean Management for Covid-19 Patient Services at Hospitals in Deli Serdang - Widya Y. Sihotang; Ermi Girsang; Silka I.N. Silangit; Sania A.F. Depari (International Journal of Health and Pharmaceutical (IJHP), 2022)
The need to improve the quality of health services in hospitals by eliminating waste in order to achieve an efficient health service process through a Lean Management approach. Methods using descriptive qualitative analysis where data is compiled, analyzed and then explained through data collection, problem solving, planning improvement ideas and by providing design improvement proposals. The application of this lean hospital reduces the service time for Covid-19 patients at Deli Serdang Hospital by 467.4 seconds in the service flow and the application of this lean hospital can reduce the service time for Covid-19 patients at the Haji Hospital by 377 seconds in the service flow. The conclusion of the study is that the application of the Lean Management approach at Deli Serdang Hospital and Haji Hospital is able to increase the effectiveness and efficiency of health services.